Advanced Metering Infrastructure for Industrial Natural Gas Smart Management - Camoleze De Araujo, Everton [UNESP]; De Almeida, Nelson Camilo [UNESP]; Godoy, Eduardo Paciencia [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
One of the challenges within the utilities sector is the development of robust, scalable and low-cost methods for the remote management of customers usage and billing. Considering the advances related to the Internet of Things (IoT), an Advanced Metering Infrastructure (AMI) is the basis for utilities smart management. This AMI bring together the automation of remote metering and communication infrastructures with the processing and analysis of distributed data using advanced techniques and cloud computing. This paper presents the development of an AMI for the smart management of natural gas industrial customers using IoT. The AMI architecture is based on the LoRaWAN communication for remote metering and a cloud-based smart management system including supervisory control, continuous monitoring, anomalies detection and alarm notification. Experimental results shown the LoRaWAN fulfilled the communication requirements for industrial natural gas metering and the smart management system can analyze historical data and detect anomalies in gas consumption
Keywords: Anomaly Detection; Internet of Things; LoRaWAN; Natural Gas Measurement